Study of the Potential Uses of Hydrochar from Grape Pomace and Walnut Shells Generated from Hydrothermal Carbonization as an Alternative for the Revalorization of Agri-Waste in Chile - Sanchez-Poblete, J; Garrido-Lazo, R (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
A myriad of resources and efforts have been devoted to assessing the possibilities of using locally sourced biomass to produce energy, reduce CO2 emissions, and, in turn, lower dependance on petroleum. Grape pomace (GP) and walnut shells (WS) are organic waste generated in Chile. Within the last decade, the potential benefits and application of biomass have received significant attention, both in terms of producing functionalized carbon materials, and the various potential applications in the field of energy storage and environmental protection. The proposed research motivation is on the development of carbonous materials through thermal decomposition processes. Few researchers have addressed the idea of developing a multipurpose carbonaceous matrix from hydrochar, and there remains a need for an efficient method to obtain hydrochar specially from grape pomace. Hence, the general objective of this research is to study the potential of grape pomace and walnut shells treated with hydrothermal carbonization (HTC) as an alternative low-cost and efficient carbonous matrix. Proximate and elemental analysis was determined to distinguish the nature of the feedstock along with the hydrochar produced. Yield and reaction severity were also studied to study the impacts of temperature and residence time for both feedstocks. Successful results from the proposed work have broad applications for increasing the sustainability biomass applications, contributing to a positive economic impact. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.